2006
DOI: 10.1007/s10722-004-4004-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity in Oil Palm (Elaeis guineensis Jacq.) using Restriction Fragment Length Polymorphism (RFLP)

Abstract: A total of 359 accessions of oil palm (Elaeis guineensis Jacq.) originating from 11 African countries (Nigeria,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In relation to the countries and regions of higher diversity, MAIZURA et al (2006) found that the populations of Nigeria presented the higher average number of alleles per loci and the higher percentage of polymorphic loci, coinciding with the results of HAYATI et al (2002) that found the higher diversity in Cameroon and Nigeria. It is proposed that Nigeria is the center of diversity of African oil palm, which is also sustained in the fact that as the geographical distance increases, the indexes of diversity decrease.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…In relation to the countries and regions of higher diversity, MAIZURA et al (2006) found that the populations of Nigeria presented the higher average number of alleles per loci and the higher percentage of polymorphic loci, coinciding with the results of HAYATI et al (2002) that found the higher diversity in Cameroon and Nigeria. It is proposed that Nigeria is the center of diversity of African oil palm, which is also sustained in the fact that as the geographical distance increases, the indexes of diversity decrease.…”
Section: Introductionsupporting
confidence: 84%
“…The studies of PURBA et al (2000); MAIZURA et al (2006) and COCHARD et al (2009), that analyzed the genetic diversity of collections of African oil palm by AFLPs, RFLPs and microsatellites respectively, found that the 'Deli' germplasm constitute a differentiated group with scarce genetic diversity. MAIZURA et al (2006) estimates a loss of 36 alleles in the Deli dura in relation to natural populations ;and HAYATI et al (2004) found that the population 'Deli' did not present rare alleles or intermediate genetic frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The mean number of alleles (A o = 2.958) and effective number of alleles for the respective oil palm groupings (A e = 2.445) was relatively higher than the values (A o ≤ 2.0) reported using different marker techniques such as RFLP (Maizura et al, 2006) and isozymes (Hayati et al, 2004;Purba et al, 2000). SSRs have revealed more alleles than other marker techniques.…”
Section: Mean Nmentioning
confidence: 65%
“…is indigenous to Africa and specifically, endemic to the South-Eastern States of Nigeria (Maizura et al, 2006;Bakoumé et al, 2015). The most important products of the crop are palm oil and palm kernel oil.…”
Section: Introductionmentioning
confidence: 99%
“…Generally the information on diversity and population structure of E. oleifera germplasm is still limited [5][6][7] compared to the E. guineensis germplasm which has been well characterised using variety of molecular markers such as isozymes [8]; RFLPs [9], SSRs derived from expressed sequence tags [10], genomic based SSRs [11] and SNPs [12]. The present study aims to unravel the population structure of MPOB E. oleifera germplasm collections using the model-based method.…”
Section: Introductionmentioning
confidence: 99%